EVALUATION OF MICROSPHERE OF POLY(LACTIC ACID) AS CELECOXIB CARRIER - nurhayati, lany; Achmadi, Suminar S.; Sudaryanto, Sudaryanto (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2024)
Celecoxib, cyclooxygenase-2 inhibitor approved for the management of rheumatism and osteoarthritis. Celecoxib is a Biopharmaceutics Classification System (BCS) class II compound whose oral bioavailability is highly limited owing to its poor aqueous solubility. Microencapsulation is very helpful to increase the solubility and slow the release of drugs. For the drugs of BCS Class-II, we use this technique which enables us to get more solubility and increase dissolution profile. The present study aims to reduce the drugâ€™s negative effect and boost its bioavailability. Poly(lactic acid) (PLA) a biodegradable polymer microsphere that can be synthesized to encapsulate celecoxib, was prepared by solvent evaporation with chloroform were used. The characterized surface morphology, drug entrapment efficiency (DDE), and in vitro drug release. Morphology was studied by scanning electron microscopy (SEM), crystallinity was studied using an X-ray diffractometer (XRD), and drug release was spectrophotometer UV-Vis. The results were observed to indicate there were microspheres homogeneous in the distribution of celecoxib in the polymer matrix. Formulations indicated that DEE was between 55.80 and 70.70% with prolonged length microspheres in the 10-30 Âµm range. Study in vitro drug release, when placed in phosphate buffer (pH 7.4) containing 2% w/w Tween 80 solvent, there was an initial burst of drug release within the first two hours followed by constant drug release. The PLA microsphere can release the confined celecoxib gradually but does not follow a controlled diffusion mechanism, but rather a mechanism of expansion and erosion of the microsphere matrix.